Impelementation of Islamic Univercity Libraries in Digital 4.0 - Rahmat Iqbal, Faizafati Matus Zahro, Eni Amaliah, Nadya Amaliah Sholeha, (UIN Raden Intan Lampung, 2024)
Islamic universities are a fragmentation of the progress of civilization that occurred during the heyday of Islam in Andalusia and Europe. The purpose of this study is to narrate the development of the Islamic world of science until the emergence of an Islamic university in the digital era. This research uses a qualitative descriptive approach. In the process of collecting data, researchers used literature review and documentation. In the era of the industrial revolution 4.0 must be able to start using strategies and also directed and measurable planning. As happened in the era of the industrial revolution 1.0, the library was still very manual in terms of services and archiving user data which began using books, borrower bags, and traditional search tools using classification numbers that were directly searched on the shelves. Furthermore, in the 2.0 era the library has started using an automation system that makes it easier to find the information needed by users, while in the 3.0 era the library has started working together to form a database until it continues until the 4.0 era the library is based on user empowerment. When viewed with the development of libraries today, especially college libraries, of course they already have policies in facing the industrial revolution era. The college library has a background as a broad reference source and has collections in printed and electronic form to support teaching, learning and research activities. One of them is by following this revolutionary era which is very beneficial for other university libraries, this is done to make it easier for the community or students to find the information they need, not only that, through this technological development, the library can also establish information and communication with other libraries widely so that it has a positive impact on increasing library accreditation.